ANTIMICROBIAL AND PHYTOCHEMICAL EVALUATION OF CISSUS QUADRANGULARIS L. - Kumar Sarkar, *Biresh; Kumar, Ravi; Kumar, Vikas; Dr, Reeta; Pal, Shashi; Krishna, C. Murali; Verma, S. C.; Singh, Ravindra; Maddi, Ramaiah (International Journal of Ayurveda and Pharma Research, 2018)
The present investigation involves antimicrobial and phytochemical evaluation of Cissus quadrangularis L. The antibacterial activity of Cissus quadrangularis was performed using disk diffusion method. The Results of study proved prompt efficacy of herbal extract against S. aureus and E. coli. The concentration dependent antibacterial activity of extract was observed against both organisms. Study also involves phytochemical investigation of herbal extract using HPTLC, IR and UV-Visible spectrophotometer. The result of study indicated that the methanolic extract possessed most potent antibacterial activity as compared to other extract. The antibacterial activity increases with the concentration and results indicated that the diameters of zone inhibition of the extract were comparable with the standard drug. The antimicrobial potential of plant extract may be attributed to the presence of specific phytoconstituents.